The Secondary Metabolites Screening and the Effectiveness (Ananas comosus (L.) Merr of the Queen Pineapple Stems in Decreasing the Number of Enterococcus faecalis’s Colonies - Shinta Nurmaraya Febrianti; Twi Agnita Cevanti; Henu Sumekar (Denta Journal Kedokteran Gigi, 2016)
Background: A cause of endodontic treatment failure was sterilization process error so that bacterias still left in the root canal. Enterococcus faecalis were resistant to sterilization medicines, it was necessary to develop natural sterilization medicines such as the Queenpineapple stems that had the antibacterial content. Purpose: The aim of this research was to determine the effectivity of the Queen pineapple (Ananas comosus (L.) Merr) stems extract in decreasing the Enterococcus faecalis’s colonies Materials and Methods: This research was true experimental with the post test only control group design. The Queen pineapple stems extract tested its secondary metabolites contents. Enterococcus faecalis ATCC 29212 cultured in Brain Heart Infusion Broth synchronized with Mc Farland 0,5 solution and divided into seven groups (n=7). It used dilution series method, each BHIB tube given by the 100% extract (P1); 50% (P2); 25% (P3); 12,5% (P4) ; 6,25% (P5) ; 3,125% (P6) and without the extract (K(-)), incubated for 24 hours and streaked on Mueller Hinton Agar and incubated for 24 hours, then calculate the colonies’ amount of each group. Datas analyzed by Mann-Whitney U-Test because only 50% and 25% concentration can be calculated. Result: The resultshowed that the Queen pineapple stems contained flavonoids, tannins, alkaloids, saponins, also there were significant differences among the 50% and 25% concentration groups p<0.05. Conclusion: The Queen pineapple stems extract’s 50% concentration was effective to decrease the number of Enterococcus faecalis’s colonies.